Basic Principles and Steps of Types of Software Models - Kaur, Ramanpreet; Singh, Satnam; singh, Harvinder; *, Divya (IJRDO -Journal of Computer Science Engineering, 2017)
Software development life cycle (SDLC) is a method by which quality software can be developed in the given time and according to the customer expectations. SDLC ensures quality product. Software Development Life Cycle Models are frameworks used to design, develop and test the software. They define a set of guidelines which are to be followed during the development. These models make sure that the software is designed systematically, according to the need of the customer and within the time schedule. Different types of software development life cycle models are waterfall, iterative, V-shaped, prototype and spiral model. Each of these models has its own benefits and drawbacks